2013
DOI: 10.1155/2013/529458
|View full text |Cite
|
Sign up to set email alerts
|

Current Understanding on Antihepatocarcinoma Effects of Xiao Chai Hu Tang and Its Constituents

Abstract: Xiao Chai Hu Tang (XCHT), a compound formula originally recorded in an ancient Chinese medical book Shanghanlun, has been used to treat chronic liver diseases for a long period of time in China. Although extensive studies have been demonstrated the efficacy of this formula to treat chronic hepatitis, hepatic fibrosis, and hepatocarcinoma, how it works against these diseases still awaits full understanding. Here, we firstly present an overview arranging from the entire formula to mechanism studies of single her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 76 publications
0
21
0
Order By: Relevance
“…With respect to Xiao-Chaihu-Decoction, a famous prescription in Shanghanlun [27] has been suggested to be workable for the treatment of breast cancer, type 2 diabetes, chronic glomerulonephritis, and so forth [28–30]; it has also been proved to be effective in the treatment of liver diseases because it can block the development of hepatitis to liver fibrosis and further to prevent the process of liver cancer through various pathways [31]. Related in vivo mechanisms include the following: inhibiting the replication of hepatitis virus, protecting liver cells, preventing liver damage, suppressing liver fibrosis, and immune regulation and antitumor effect [32–34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to Xiao-Chaihu-Decoction, a famous prescription in Shanghanlun [27] has been suggested to be workable for the treatment of breast cancer, type 2 diabetes, chronic glomerulonephritis, and so forth [28–30]; it has also been proved to be effective in the treatment of liver diseases because it can block the development of hepatitis to liver fibrosis and further to prevent the process of liver cancer through various pathways [31]. Related in vivo mechanisms include the following: inhibiting the replication of hepatitis virus, protecting liver cells, preventing liver damage, suppressing liver fibrosis, and immune regulation and antitumor effect [32–34].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Xiao-Chaihu-Decoction may be involved in antihepatic fibrosis via inhibiting the activation of hepatic stellate cells, synthesis of collagen, and induction of correlated mRNA expression in the liver, further decreasing platelet-derived growth factor and growth factor B1, both of which are important factors for stimulating the formation of liver fibrosis and preventing liver fibrosis development to cirrhosis and eventually to liver cancer [35]. Most importantly, PLC is a disease that mainly correlated with HBV or HCV infections, Xiao-Chaihu-Decoction has obvious anti-HBV effect, and anti-HBV mechanism of Xiao-Chaihu-Decoction may be achieved by regulating the immune system [31, 36]. Besides, Xiao-Chaihu-Decoction may be responsible for the inhibition of the cell cycle G0/G1 stage of cancer cell line, as well as direct suppression of cell proliferation and apoptosis by human immune-deficiency virus infection, thereby inhibiting the transformation of liver cirrhosis to cancer, removing reactive oxygen species in a dose dependent manner, and suggesting an inhibitory effect in the initial stage of carcinogenesis [33, 37].…”
Section: Discussionmentioning
confidence: 99%
“…Xiao Chai Hu Tang (XCHT), a well-known Chinese Traditional Medicine, is made from seven herbals including Bupleurum falcatum, Panax ginseng, Glycyrrhiza glabra, Zingiber officinale, Scutellaria baicalensis, Zizyphus jujube, and Pinellia ternate [1, 2]. This famous formula was initially recorded in the ancient medicinal book named Shanghanlun 2000 years ago [3].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies in cell lines and in vivo studies in animal models suggested that XCHT has multiple pharmacological functions including inhibition of hepatitis virus [5, 6], anti-inflammatory [710], immune-modulating [7, 11], liver protective effect [12, 13], anti-cancer [2, 14, 15], and renal protective effect [16]. Clinical trials demonstrated that XCHT improved liver pathology in patients with chronic viral hepatitis [2, 11, 17, 18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation